An Analysis of Second Grade Students’ Pronunciation Through Phonics-Based Learning - Citra, Lely (Journal of Linguistics and Social Sciences, 2025)
This study investigates the use of phonics-based learning to improve English pronunciation among Grade Two students at SDN 2 Sukarame, Lampung. The findings reveal that prior to phonics instruction, students often mispronounced words due to relying on Bahasa Indonesia pronunciation rules and lacking awareness of letter–sound relationships. After the intervention, students demonstrated notable improvements in producing correct sounds, distinguishing similar phonemes, and reading more fluently. Pair work, visual materials, and multisensory activities enhanced engagement and confidence. Nevertheless, challenges persisted with unfamiliar sounds such as /θ/ and /ð/, limited lesson time, and varying levels of home practice. The study concludes that phonics-based learning can significantly enhance young learners’ pronunciation and reading fluency when integrated with interactive strategies, parental involvement, and culturally relevant materials. Recommendations include providing additional time for practice, targeted pronunciation drills for difficult sounds, and stronger collaboration between school and home.